Dental diseases and factors defining utilization of dental care services among rural children aged 12 years in Nellore District, Andhra Pradesh: A community-based study - Chandrasekhara Reddy Vuyyuru; Rajeshree Narayan Rangari; Gowri Sankar Singaraju; Nagarjuna Pottem (Wolters Kluwer Medknow Publications, 2021)
Background: Rural children are predisposed to variety of dental problems, which may influence their overall health and well-being. Despite relentless efforts and achievements in oral health promotion by authorities, its impact seems limited in rural areas of developing countries. Aim: To generate data on the prevalence of dental caries and gingivitis, among 12-year-old rural children of Nellore district, Andhra Pradesh and factors facilitating or impeding uptake of dental care services. Methods: A cross-sectional, house-to-house survey was conducted in Kavali revenue division of Nellore district by random selection. A cluster sampling methodology was followed, and a total of 169 adolescents were involved in the study. Dental caries detection was performed according to the World Health Organization dentition status criteria and gingivitis according to modified Community Periodontal Index as gingivitis present or absent. Descriptive statistics were calculated. Results: Overall prevalence of dental caries and gingivitis was 39% and 35%, respectively, with <15% utilization of oral health care services. The main hurdle for this notably low utilization of oral health care services was that dental issues were not fatal or life-threatening. Conclusion: The prevalence of dental caries and gingivitis was high and poor utilization of oral health services was an importunate finding in this study. Understanding the trends of common oral diseases and hurdles in uptake of oral health care services could provide a basis for further research and improvement in accessibility to oral health care services in rural areas of developing nations.